Occasional spontaneous clearance of chronic hepatitis C virus in HIV-infected individuals - Stenkvist, Jenny; Nyström, Jessica; Falconer, Karolin; Sönnerborg, Anders; Weiland, Ola (Journal of hepatology, 2014)
The IL28B genotype has been found to have a strong influence on spontaneous clearance of acute HCV both in HCV mono- and HIV/ the HCV co-infected patients. Spontaneous clearance of chronic HCV without HCV treatment is rare. Here, we report on three chronic HCV cases co-infected with HIV with spontaneous clearance of their HCV infection, all with the IL28B CC genotype. These cases were derived from a surveillance of the total HIV/HCV co-infected cohort in Sweden (n=466). The estimated frequency of spontaneous clearance of chronic HCV infection in our cohort was calculated to be 0.6–4.7%. Our cases lend some support to the initiation of ART prior to HCV treatment in HIV/HCV co-infected patients. Furthermore, HCV-RNA testing should be recommended immediately before initiation of HCV treatment, to find the subset of HIV/HCV co-infected patients with IL28B CC that may have cleared their chronic infection spontaneously.